Impact of Trade Openness on Tax Revenue in Transitional Markets - Tsaurai, Kunofiwa (The Journal of Accounting and Management, 2024)
This paper explored the influence of trade openness on tax revenue in transitional markets employing panel methods with data spanning from 2005 to 2020. It also examined the impact of interaction between trade openness and financial development on tax revenue in transitional markets using the same panel methods and data set. The influence of trade openness on tax revenue under fixed effects, random effects and dynamic GMM (generalized methods of moments) was positive and significant. Trade openness’ impact on tax revenue was positive but non-significant in transitional markets according to pooled (OLS). Financial development also significantly enhanced tax revenue under dynamic GMM, random and fixed effects and non-significantly increased tax revenue under the pooled OLS. Complementarity variable nonsignificantly improved tax revenue under the pooled OLS whereas other remaining methods show a significant positive relationship running from the complementarity variable towards tax revenue. Financial development is therefore a channel facilitating trade openness’ impact on tax revenue in transitional markets. Policy implication is that transitional markets should implement policies and strategies aimed at enhancing trade openness and financial development to be able to generate more tax revenue.